(NoSNOWY RADIO\LEKTRONIKI (B:s (Nu^EBNOE POSOBIE (B/s - (NmANAEW(B, (NeWGENIJ iWANOWI^s ((NmOSKWA (B:s (NrADIO I SWQZX(B,s, 1985)
(NbIBLIOGR(B.: (NS(B. 496-497 (55 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 498-499s
Keywords: (NrADIO\LEKTRONIKAs